Pengaruh Kualitas Produk, Promosi Diskon, Dan Kemudahan Pembelian Terhadap Minat Pembelian Ulang Produk Kecantikan Ms Glow Di Kota Surabaya - Ike Nur Fadlilah; Evi Thelia Sari; Leonard Adrie Manafe (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This research aims to analyze the influence of product quality, discount promotions, and ease of purchase on the repurchase intention of Ms Glow beauty products in Surabaya City. The research method used is a quantitative approach with purposive sampling technique. Data were collected through questionnaires distributed to Ms Glow consumers in Surabaya City who have made at least one purchase. The results show that product quality, discount promotions, and ease of purchase have a positive and significant effect on repurchase intention both partially and simultaneously. Based on the results of multiple linear regression analysis, it is known that the three independent variables together contribute 65.3% to the repurchase intention, while the remaining is influenced by other factors outside this study. This finding has implications for beauty business players, especially Ms. Glow, to improve product quality, optimize discount promotion strategies, and facilitate access to purchases to increase customer loyalty.